Nilai-Nilai Profetik Dalam Pendidikan Islam: Analisis Konsep Tarbiyah Qur’aniyyah Dalam Tafsir Al-Azhar Karya Buya Hamka - Mulyani, Sri; Yusuf, Enjang Burhanudin (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This article examines prophetic values in Islamic education through an analysis of the concept of tarbiyah Qur’aniyyah in Buya Hamka’s Tafsir Al-Azhar. The study aims to identify and analyze the dimensions of humanization, liberation, and transcendence reflected in Hamka’s interpretation of educational verses, particularly QS. Luqman: 13–19, QS. Al-‘Alaq: 1–5, and QS. Al-Ahzab: 21. This research employs a qualitative library approach using thematic Qur’anic interpretation (maudhu‘i) and content analysis of the tafsir text. The findings indicate that tarbiyah Qur’aniyyah in Tafsir Al-Azhar emphasizes the dignity of humanity through moral and ethical formation, the liberation of human beings from ignorance through literacy and knowledge development, and the strengthening of a transcendental orientation as the foundation of education. These findings highlight Islamic education as a holistic and integrative process rooted in Qur’anic values